From Antiquity to the Paris Commune: S. A. Ljaskowski at the Belarusian State University - Maliugin, Oleg I. (Journal of the Belarusian State University. History, 2022)
S. A. Ljaskowski is a representative of the generation of Moscow University graduates of the early 20th century, whose formation as scientists and teachers fell on the years of the war and revolution. As a student of R. Yu. Vipper, he specialised in Ancient and Early Medieval periods. In the first years after revolution, he began teaching at provincial Russian universities, and from 1924 to 1927 he worked at the Belarusian State University. It was his work at this university that became a kind of watershed – when S. A. Ljaskowski had to re-profile from Ancient and Medieval history to the Modern and Contemporary history, both in teaching and in scientific interests. But he also failed to gain a foothold in the Belarusian State University – the courses he taught looked much more organic in the load of new teaching staff, who often did not have a university education, but were able to boast of a «correct» origin and revolutionary background. As a result, he did not manage to return to fullfledged scientific work in the field of his specialisation after his dismissal from Belarusian State University, having published in the 1930s. Only a few articles on the history of antiquity and gradually retraining for reviews of foreign and Soviet literature on the history of the ancient world and, subsequently, for bibliographic work.
Keywords: S. A. Ljaskowski; Belarusian State University; Medieval studies; history of Antiquity